Developing an augmented reality based interactive module for lessoning curvent side space building - Sabrina, Agtya Jacklione; Sumardi, Sumardi (Universitas Islam Negeri Raden Intan Lampung, 2024)
In previous research, it was found that the incorporation of AR technology has the potential to improve the way people learn in curved spaces and make it easier for students to visualize shapes. This makes a solution to the problem of students found by researchers in the field that students find it difficult when learning curved spaces without the help of props. However, students also say that the use of physical form props is not practical to use. Therefore, the goal of this research is to develop valid, effective, and practical augmented reality-based interactive learning materials for use in curved space learning. This product is developed using the ADDIE model. Data were collected through student response questionnaire instruments and pre-test post-test questions. Data analysis was conducted to determine the validity of the product using the Aiken Value, the level of effectiveness obtained through the n-gain score, and practicality using the mean value and TCR of the student response questionnaire score. It was found that the product was classified in the